2010
DOI: 10.1128/jvi.00554-10
|View full text |Cite
|
Sign up to set email alerts
|

A Single Asparagine-Linked Glycosylation Site of the Severe Acute Respiratory Syndrome Coronavirus Spike Glycoprotein Facilitates Inhibition by Mannose-Binding Lectin through Multiple Mechanisms

Abstract: Mannose-binding lectin (MBL) is a serum protein that plays an important role in host defensesA novel coronavirus (CoV), severe acute respiratory syndrome-CoV (SARS-CoV), is the causal agent of severe acute respiratory syndrome, which afflicted thousands of people worldwide in 2002 and 2003 (10, 39). SARS-CoV is an enveloped, single-and positive-strand RNA virus that encodes four major structural proteins: S, spike glycoprotein (GP); E, envelope protein; M, membrane glycoprotein; and N, nucleocapsid protein (46… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
159
1
4

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 143 publications
(172 citation statements)
references
References 73 publications
(84 reference statements)
5
159
1
4
Order By: Relevance
“…rcMBL acts by direct binding the viral glycoprotein spike through its CRD, thereby aggregating virus particles. For mammalian MBL, direct virus neutralization through interaction with viral glycoproteins, thereby blocking virus binding to receptors on host cells, has been described before (Brown et al, 2010;Ip et al, 2005;Ji et al, 2005;Zhou et al, 2010). Here, we observed that rcMBL binds two IBV strains, IBV-Beaudette and IBV-M41, in line with a previous observation with an unspecified IBV strain (Kjaerup et al, 2014a).…”
Section: Discussionsupporting
confidence: 91%
“…rcMBL acts by direct binding the viral glycoprotein spike through its CRD, thereby aggregating virus particles. For mammalian MBL, direct virus neutralization through interaction with viral glycoproteins, thereby blocking virus binding to receptors on host cells, has been described before (Brown et al, 2010;Ip et al, 2005;Ji et al, 2005;Zhou et al, 2010). Here, we observed that rcMBL binds two IBV strains, IBV-Beaudette and IBV-M41, in line with a previous observation with an unspecified IBV strain (Kjaerup et al, 2014a).…”
Section: Discussionsupporting
confidence: 91%
“…Recently, this was supported in a paper by Zhou et al (2010) [31] who showed a direct MBL-mediated neutralization of severe acute respiratory syndrome-coronavirus (SARS-CoV) by blocking the binding of the virus specific S glycoprotein (SARS-S) to the DC-SIGN receptor (dendritic cell-specific intercellular adhesion molecule 3grabbing nonintegrin-related molecule) suggesting that MBL most likely recognizes an overlapping set of high-mannose-content glycans on the S glycoprotein and thereby competes with DC-SIGN for binding. DC-SIGN is known to bind to different pathogens and triggers intracellular signaling cascades that affect TLR signaling and thereby adaptive immune responses (reviewed in [32]).…”
Section: Discussionmentioning
confidence: 75%
“…2A). The remaining 8 predicted N-glycosylation sites, namely 27 NTSH, 31 NNSK, 482 NYTD, 585 NGSV, and 590 NVTS in the S1 subunit, 1308 NTTH in the S2 subunit, and 1352 NQTK and 1357 NLTA in HR2, were not verified due to the lack of corresponding tryptic peptides. To obtain an unbiased view of the range of N-glycans carried, the pool of released N-glycans was profiled by MALDI-MS after permethylation.…”
Section: Resultsmentioning
confidence: 99%
“…Site-Specific N-Glycosylation Mapped by MS and Cryo-EM. Glycosylation of CoV S proteins is implicated in protein folding (22), structure stability (22), virus entry, and receptor recognition (23)(24)(25)(26)(27). According to the sequence, 37 N-linked glycosylation sites are predicted for FIPV-UU4 S protein.…”
Section: Resultsmentioning
confidence: 99%